Parsimony Analysis of Endemicity (PAE) in Iranian freshwater basins based on subterranean amphipods genus Niphargus (Crustacea, Malacostraca) - Somayeh Esmaeili-Rineh (Iranian Journal of Animal Biosystematics, 2020)
The order Amphipoda is one of the most diverse taxa that globally distributed in all environments and virtually habitats. The members of genus Niphargus represent an important part of the Western Palearctic subterranean amphipoda fauna. Accurate data on the occurrence and distribution of amphipods are only available for some regions. In this study, we were applied Parsimony analysis of endemicity (PAE) to analyze the distribution of amphipod freshwater genus Niphargus occurring strictly at the basin or sub-basin level along of Elburz and Zagros Mountains in Iran. The analysis was carried out using the computer program PAUP* 4.0a166, based on a data matrix built with 27 taxa and 13 areas for genus Niphargus. The rooting was made on a hypothetical all-zero out-group. Applying the exact algorithm heuristic search, the consensus tree was obtained with 30 steps, a consistency index of 0.9, and a retention index of 0.1. The procedure based on distributions of the 27 species of Niphargus delimited five areas of endemism in the study area with minimum two species. The high levels of endemism observed in West boundary rivers1 sub basin with six species and then in Urmia and West boundary rivers2 sub basins with three species.